PMO-163 Fibroscan delineates significant fibrosis better than the King's Fibrosis Score, APRI and FIB4 score when correlated to liver biopsy in a large monocentric cohort of hepatitis C patients. (28th May 2012) - See, L-M; Kok, B; Kamparidis, N; Badot, M-A; Hodgson, S; Carey, I; Joshi, D; Heneghan, M; Harrison, P; Agarwal, K
Abstract : Introduction: In the context of consideration of antiviral therapy for hepatitis C virus (HCV), fibrosis assessment is critical. An increasing array of non-invasive blood panels are in use; in addition Liver Stiffness Measurements (LSM) by Fibroscan is an established clinical tool in some clinical centres. Liver biopsy is however still perceived as the "silver" standard for fibrosis assessment in HCV. The aim of our study was to evaluate the diagnostic accuracy of LSM, King's Fibrosis Score (KFS), APRI (aspartate aminotransferase to Platelet Ratio) and FIB4 score (age, platelets, aspartate aminotransferase and alanine aminotransferase) in predicting significant fibrosis (Ishak score F3–F6) and cirrhosis (F5–F6) in a large monocentric cohort of HCV patients. Methods: Retrospective data collection was performed on 484 patients with hepatitis C that underwent both Fibroscan and liver biopsy at King's College Hospital between November 2006 and November 2011. Data were analysed to correlate liver biopsy results with LSM, KFS, APRI and FIB4 score. Each biopsy was assessed via Ishak score with three specialist Liver Histopathologists. All Fibroscans were performed by two trained operators. Each test was correlated against liver biopsy findings using ROC curves, sensitivity and specificity. Results: For predicting significant fibrosis (F3–F6), the area under receiver operating curves 95% CIs were 0.81 (0.77 to 0.85, p<0.001) for LSM; 0.71 (0.66 to 0.76, p<0.001) for KFS; 0.71 (0.66 to 0.76, p<0.001) for APRI and 0.79 (0.73 to 0.84, p<0.001) for FIB4 score. In the diagnosis of cirrhosis, the area under receiver operating curves was 0.83 (0.76 to 0.9, p<0.001) for LSM, 0.72 (0.64 to 0.79, p<0.001) for KFS, 0.67 (0.59 to 0.75, p<0.001) for APRI and 0.77 (0.68 to 0.85, p<0.001) for FIB4 score respectively. A LSM threshold of 7.8 kPa had a 68% sensitivity and 81% specificity to detect significant fibrosis and a threshold of 10.25 kPa had a sensitivity of 75% and a specificity of 80% in detecting cirrhosis. Conclusion: In our real-life monocentric HCV population, liver stiffness measurement via Fibroscan performed best in prediction of both moderate fibrosis and cirrhosis in comparison to the KFS, APRI and FIB4. However, all these panels performed reasonably in delineating significant fibrosis and cirrhosis. An increased availability of Fibroscan, coupled with non-invasive fibrosis panels in primary or outreach settings can radically improve the clinical assessment and evaluation of HCV patients for HCV therapy, while also defraying cost and improving safety and acceptability from a patient perspective. Non-invasive fibrosis assessment needs to be widely available. Competing interests: None declared.